Nanoengineered-based delivery systems to modulate CD4+ T cell responses in cancer: emerging paradigms in cancer immunotherapy - Shahreen, Nekhat; Agnihotri, Anukrati; Rizwan, Asfi; Hasan, Faizul; Ansari, Mohd Danish; Sofian, Zarif Mohamed; Said, Nur Akmarina B. M.; To, Kenneth K. W.; Mahmood, Syed (Frontiers in Pharmacology, 2025)
BackgroundCD4+ T-cells play a pivotal role in cancer immunology, functioning as both tumor-suppressing and tumor-promoting agents depending on their differentiation and cytokine profiles. Targeting CD4+ T-cells with novel drug delivery systems, particularly nanoparticle-based formulations, offers a promising approach to enhancing antitumor immune responses while minimizing systemic toxicity.ObjectiveThis review aims to explore the immunological significance of CD4+ T-cells in cancer and their modulation using novel drug delivery systems. The focus is on understanding CD4+ T-cell subtypes, their functional roles in tumor progression and suppression, and the application of novel drug delivery systems to selectively regulate these cells.MethodsA comprehensive analysis of CD4+ T-cell subsets, including Th1, Th2, Th17, Tregs, and Tfh, was conducted, along with their immunological roles in cancer. Various nanoparticle platforms, including liposomes, polymeric nanoparticles, dendrimers, gold, silver, and mesoporous silica, were evaluated for their ability to target CD4+ T-cells.ResultsNovel drug delivery systems demonstrate significant potential in selectively modulating CD4+ T-cell responses. Liposomes and polymeric nanoparticles efficiently transport cytokines, antigens, as well as immunological modulators to CD4+ T-cells, enhancing antitumor immunity. Notably, MHC II-coated nanoparticles expanded antigen-specific CD4+ T-cells, while mRNA nano vaccines activated CD4+ and CD8+ responses.ConclusionNovel drug delivery systems provide a versatile platform for precise CD4+ T-cell modulation in cancer therapy, enhancing antitumor responses while reducing toxicity. Future advancements should focus on overcoming biological barriers, improving targeting, and optimizing clinical translation.